Effects of COVID-19 pandemic on colorectal cancer surgery - Uyan, Mikail; Özdemir, Ali; Kalcan, Süleyman; Tomas, Kadir; Demiral, Gökhan; Pergel, Ahmet; Tarım, İsmail Alper (São Paulo Medical Journal, 2022)
BACKGROUND: The coronavirus disease-19 (COVID-19) pandemic has changed the course of diseases that require emergency surgery. OBJECTIVE: To evaluate the effect of the COVID-19 pandemic on colorectal cancer disease stage. DESIGN AND SETTING: Retrospective analysis in the city of Rize, Turkey. METHODS: This was a comparative analysis on two groups of patients with various symptoms who underwent surgical colorectal cancer treatment. Group 1 comprised patients operated between March 11, 2019, and December 31, 2019; while group 2 comprised patients at the same time of the year during the COVID-19 pandemic. RESULTS: Groups 1 and 2 included 56 and 48 patients, respectively. The rate of presentation to the emergency service was higher in Group 2 (P < 0.02). The stage of the pathological lymph nodes and the rate of liver metastasis was higher in Group 2 (P < 0.004 and P < 0.041, respectively). The disease stage was found to be more advanced in Group 2 (P < 0.005). The rate of postoperative complications was higher in Group 2 (P < 0.014). CONCLUSION: The presentation of patients with suspicious findings to the hospital was delayed, due both to the fear of catching COVID-19 and to the pandemic precautions that were proposed and implemented by healthcare authorities worldwide. Among the patients who presented to the hospital with emergency complaints and in whom colorectal cancer was detected, their disease was at a more advanced stage and thus a higher number of emergency oncological surgical procedures were performed on tho se patients.